Application of Class-Based Characteristic Economic Teaching Materials for High School Students in Singkawang City - Purwaningsih, Endang (Jurnal Pendidikan Sosiologi dan Humaniora, 2024)
This research uses a Design Based Research (DBR) approach to develop and test Economics teaching materials with the dimension of strengthening character education for high school students in Singkawang City. The aim of this research is to produce teaching materials that not only increase understanding of economic material, but also help students internalize character values that are relevant to social, cultural and economic change. The problem faced is how to create effective and relevant teaching materials in the context of ongoing changes. The method used includes field trials with an experimental design, where the teacher applies the developed teaching materials in the learning process. The test subjects were high school students in Singkawang City, with data collected through observation and tests. Data analysis uses qualitative analysis for the field test implementation process and the Wilcoxon Test to determine the effectiveness of teaching material products. Specific results showed significant improvements in student learning outcomes, with an average pre-test score of 43.63 increasing to 55.35 in the post-test. In general, the results of this research show that teaching materials with character are effective in improving economic learning outcomes and shaping the character of students. In conclusion, the application of economic teaching materials based on strengthening character education can prepare students to become the golden generation of 2045 who excel in skills, competence and character.